Vegetação arbórea na qualidade do agroecossistema - Vanin, Jucelaine (2012)
The anthropic action exerts great influence on environments. Different forms of occupation and use of an area affect the landscape and consequently on its biodiversity and hydric resources. The study was conducted in three landscape units, with different levels of anthropogenic (high, medium and low) in the hydrographic basin. The objective of the study was to evaluate the landscape richness, especially arboreal vegetation in areas of permanent preservation (APPs) and the quality of hydric resources according to the different handlings in these landscape units.You can notice that satisfaction with the work, the love and the commitment to the territory are decisive factors so that the farmers do not leave their area, independently of the extension explored. In the high anthropogenic landscape unit it was verified more degradation of the landscape, due to the high pressure occupation of territory by the dairy activity. The biodiversity of the arboreal vegetation in areas of permanent preservation (APPs) was lower in areas of high anthropogenic in relation to areas of medium and low. The native arboreal vegetation presents a diverse and slow growth among species. The water quality is influenced by the different soil uses and by the topography studied in landscape units. Handlings predetermine the quality of the landscape. The interference in the landscape and the preservation of permanent preservation (APPs) depends on environmental awareness, but is also determined by economic issues. Farmers who practice horticulture (of subsistence) and gardening are encouraged to preserve the native vegetation.